The Role of Health Systems and Policies in Promoting Safe Delivery in Low- and Middle-Income Countries: A Multilevel Analysis - Kruk, Margaret E (American Public Health Association, 2012)
We aimed to measure the contribution of national factors, particularly health system characteristics, to the individual likelihood of professionally attended delivery (“safe delivery”) for women in low- and middle-income countries. Using Demographic and Health Survey data for 165 774 women in 31 countries, we estimated multilevel logistic regression models to measure the contribution of national economic and health system characteristics to likelihood of attended delivery. More health workers, higher national income, urbanization, and lower income inequality were associated with higher odds of attended delivery. Macrosocial factors increase utilization of attended delivery and may be more efficient in reducing maternal mortality than are interventions aimed at individual women.